APLIKASI MEDIA PROMOSI BERBASIS AUGMENTED REALITY MENGGUNAKAN METODE MARKER BASED TRACKING DI INSTITUT TEKNOLOGI DAN BISNIS BINA ADINATA - Rahmawati Rahmawati; Raden wirawan; Andi Nurul Faizah (CV. LAJAGOE PUSTAKA, 2025)
This study aims to: (1) Design augmented reality-based promotional media applications using the marker-based tracking method on the Bina Adinata Institute of Technology and Business campus. (2)Determine user response to augmented reality-based promotional applications using the marker-based tracking method at the Institute Technology and Business Bina Adinata.This study used the Multimedia Development Life Cycle (MDLC) Model method. This method has six stages, namely concept, design, material collection, assembly, testing, and distribution. Data collection techniques used in this study were observation, interviews, literature study, questionnaires and documentation. At the design stage, the android specifications for campus promotional media applications are at least Android version 11 with a RAM capacity of 3 GB.The results of the study show that:(1) The design stage of augmented reality-based campus promotional media applications uses the marker-based tracking method, starting with the design of markers and 3D objects as input. In designing application requirements there are many supporting components, namely, using the Unity software version 2022.1.20f1 to build augmented reality applications. Vuforia engine version 10.10.2 is used as a tool that can insert target images into unity 3D, where the marker used is the logo of the Bina Adinata Institute of Technology and Business. Making 3D objects for campus buildings is designed using the Sketchup 2019 software, the author uses the CorellDraw application to make the application background and the buttons. In addition, the application used is also a video editing application, namely VN and Kine Master. And the operating system used is Microsoft Windows 10. All of these components are integrated into Unity to become an augmented reality-based campus promotional media application. (2) The response of the New Student Admissions Committee (PMB) to campus promotional media applications, among others, is that this application is quite interesting, easy to use, the information presented is interesting, and can be used as a reference for campus promotional media. Based on the response of the respondents from the questionnaire that was distributed, the response was obtained in a very positive category with the results of data analysis, namely 91,09%.